Cluster of differentiation 38 monoclonal antibody therapy in the treatment of multiple myeloma: a systematic review and meta-analysis - Guo, Yan-Jun; Tian, Zhi-Zhong; Zhang, Xiao-Fen; Zhu, Zhen-Jun (Frontiers in Pharmacology, 2026)
BackgroundCluster of differentiation 38 (CD38) monoclonal antibodies, including daratumumab and isatuximab, have demonstrated clinical activity in relapsed or refractory multiple myeloma (MM). This study aims to systematically evaluate the efficacy and safety of CD38-targeted monoclonal antibodies compared with those of standard regimens.MethodsThis study searched PubMed, the Cochrane Library, Web of Science, and Embase from inception until 30 June 2025 for randomized controlled trials (RCTs) comparing CD38 antibodies (alone or in combination) with proteasome inhibitor- or immunomodulatory agent-based control regimens in adults with multiple myeloma. Two reviewers independently screened the studies, extracted data, and assessed the risk of bias (Cochrane risk of bias 2.0). Pooled risk ratios (RRs) and hazard ratios (HRs) were estimated using fixed- or random-effects models according to I2 heterogeneity. Publication bias was examined using Egger’s test.ResultsA total of eight RCTs with 2,821 patients were included. The pooled overall response rate (ORR) was significantly improved with CD38-targeted therapies (RR 1.59; 95% confidence interval [CI] 1.32–1.92; p < 0.001). Progression‐free survival (PFS) was also significantly prolonged (HR 0.50; 95% CI 0.39–0.61; p < 0.001). Subgroup analyses indicated consistent benefits across the renal function, age groups, and prior therapy lines. However, CD38-targeted therapies were associated with higher rates of non-hematologic adverse events, including infections and diarrhea.ConclusionCD38 monoclonal antibodies enhance the depth of response and prolong progression-free survival in multiple myeloma, with an acceptable safety profile, supporting their integration into treatment algorithms.